What Are the Challenges for Gastroscopy During COVID-19 Pandemic? - Cakcak, İbrahim Ethem and Ermeydan, Meltem and Altürk, Leyla and Türkmen, İrem and Göktaş, Şeymanur (Cerrahpaşa Medical Journal, 2022)
Objective: We aimed to evaluate and investigate the effects of the pandemic on gastroscopy, including indications, the procedure performed, and diagnoses made as a result of the procedure. Methods: In our retrospective study, patients who came to Trakya University Hospital to have a gastroscopy between March 2019 and March 2021 were evaluated, retrospectively. Percentages, mean, median, and quartiles were used as descriptive statistics. Mann–Whitney U test was used for the variations which are contrary to the normal distribution range in the comparison of the 2 groups. The Pearson Chi-Square and Fisher’s Exact test studied the relations between qualitative variations. The significant value was determined as .05 for all statistical analyses. Results: In our study, there were 109 patients during COVID-19 period and 268 patients during the pre-COVID-19 period. The mean age was 55.5 for the pre-COVID and 56.6 for the COVID period. The rate of patients who underwent percutaneous endoscopic gastrostomy during pre-COVID was 14.17% and during COVID period, it was 19%. The rate of re-admissions to the hospital with malignant pathology of patients who had previously been operated on for malignant reasons was 5.26% during Pre-COVID and 11.81% during COVID period (P < .001). Conclusions: During the COVID-19 period, we observed that patients applied late because they were afraid of coming to the hospital even if they had symptoms. More scheduled health services will provide better results for both patients and health personnel in such epidemic periods. Cite this article as: Cakcak İE, Ermeydan M, Altürk L, Türkmen İ, Göktaş Ş. What are the challenges for gastroscopy during COVID-19 pandemic? Cerrahpaşa Med J. 2022;46(3):258-262.